Ku filozofii przyjaźni. W dialogu z Platonem, Arystotelesem i św. Teresą od Jezusa. Część III. - Wach, Albert Stanisław (Itinera Spiritualia. Commentarii Periodici Instituti Carmelitani Spiritualitatis Cracoviae, 2019)
The article constitutes the third part our study of the philosophy of friendship. It presents a sort of dialogue between three great experts in this field: Plato, Aristotle and St Teresa of Avila. They gave testimony to the central place of the idea of friendship in their respective times, and they help modernity to retrieve it. The first point in the third part of this study takes up again the question of the interpersonal relationships, and, specifically, describes various types of friendship (3.4). St Teresa distinguishes only two types of friendship, whereas Aristotle speaks of three. Their reflections have an existential value in that they help us to distinguish authentic from inauthentic forms of friendship.The study proceeds by considering friendship as virtue (3.5) and friendship as affection (or passion) (3.6). These two concepts are fundamental for understanding friendship as such. The first (virtue) brings out the ideal significance of friendship.The second (passion) speaks of its significance in reality. These meanings are distinct, but not opposed.The final point of this study, and the final element in the dialogue between Teresa and Aristotle, picks up again the question of the two related but distinct concepts, namely “friendship” and “love” (3.7).